Analisis Manajemen Resiko Aplikasi SIPP di Pengadilan Negeri Salatiga Kelas 1B Mengunakan ISO 31000 - Ryan Haryo Pangestu; Ariya Dwika Cahyono; Penidas Fiodinggo Tanaem (Journal of Computer and Information Systems Ampera, 2021)
SIPP application is a case tracing information system whose function is to provide information to the general public or severe parties concerned with the case and the information contained in sipp has been adjusted to the applicable regulations. In implementing the information system there must be risks that hinder the process of the system, so here is required risk analysis aimed at preventing or minimizing the risks that will occur. By using ISO 31000 at salatiga district court office, it is expected to minimize the possibility of risks that will occur around SIPP application. The results will be from iso 31000 risk analysis in the form of a document of possible risks that occur around sipp application, grouping the possible risks and their impacts. So that the results of this research can be useful for the salatiga district court office to prevent or at least minimize the risks that may occur in the SIPP application.